2008
DOI: 10.1016/j.jtcvs.2007.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Predictors affecting durability of epicardial pacemaker leads in pediatric patients

Abstract: Epicardial leads provide a reliable technique for managing rhythmic disturbance problems in the pediatric population. The only significant predictor of lead failure is the presence of structural heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
0
20
2
Order By: Relevance
“…However, in the presence of (relative) contraindications for the transvenous approach, such as small body size, an intra-cardiac shunt or absence of a venous access, an epicardial lead implantation is preferred despite the high rate of lead failure. The estimations of lead longevity vary widely, and seems to be difficult to predict whereas different risk factors for lead failure had been described [3][4][5][6][7][8][9][10]. In our study, we found an incidence of lead failure of 2.3% per lead per year of follow-up.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…However, in the presence of (relative) contraindications for the transvenous approach, such as small body size, an intra-cardiac shunt or absence of a venous access, an epicardial lead implantation is preferred despite the high rate of lead failure. The estimations of lead longevity vary widely, and seems to be difficult to predict whereas different risk factors for lead failure had been described [3][4][5][6][7][8][9][10]. In our study, we found an incidence of lead failure of 2.3% per lead per year of follow-up.…”
Section: Discussionmentioning
confidence: 60%
“…Fortescue et al found that a lower age (< 12 years) at first implant and the presence of structural congenital heart disease were both independent predictors for reduced lead longevity with an HR of 2.7 (p<0.001) and 1.8 (p=0.007), respectively [11]. The presence of structural congenital heart disease as an independent predictor for lead failure was confirmed by Murayama et al The patient's age at implantation was not a predictor for lead failure in their study [6]. In our study we could not find an association between the presence of a structural heart disease and the occurrence of lead failure.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…9,10 Epicardial lead sites can be also be problematic because patients frequently have extensive epicardial scarring because of multiple re-entry sternotomies and may have surgical patches or extensive atrial suture lines limiting availability of an appropriate epicardial site for lead implantation. [2][3][4][5][6][7][8] Transmural placement of atrial pacing leads has been previously described [11][12][13][14] and has been performed on selected patients at our institution since 1998. The present analysis of chronic TMA lead performance validates the use of this approach as a practical and appropriate treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…This study does not account for multiple potential confounding variables that may affect lead performance although these would largely tend to have a negative effect on lead performance, which was not observed in this study. 2,5,15 Finally, it is conceivable that placement of the TMA lead, while relatively focal, could contribute to postoperative IART, as might be the case for any surgical scar/barrier.…”
Section: Limitationsmentioning
confidence: 99%